Incorporation of Nanochitin in Cement Mortars: An Approach to Enhancing Durability and Sustainability - Alvansazyazdi, Mohammadfarid (2025)
Abstract This study explores the use of nanochitin extracted from crab shell waste to enhance the mechanical and durability properties of cement-based mortars. Nanochitin, a biopolymer derived from chitin, has been identified as a promising nanomaterial additive that improves compressive strength, cohesion, and workability of cementitious composites. The methodology involved the synthesis, characterization, and incorporation of nanochitin in mortars using Type N and Type HS cements. The mechanical performance was evaluated through uniaxial compression tests, permeability analysis, and microstructural characterization via Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD). The results indicate that nanochitin enhances hydration, contributing to an optimized cementitious matrix. The modified mortars exhibited higher compressive strength, reaching 9.18 MPa at 90 days in Type N cement. Furthermore, nanochitin demonstrated superior rheological properties, allowing for improved workability and water retention, particularly in arid environments. This study highlights the sustainability benefits of repurposing crab shell waste, aligning with circular economy principles and advancing the development of eco-friendly construction materials.